ADAPTATION OF ORIENTAL REALITIES IN RUSSIAN AND ENGLISH LITERARY TEXT - Kulmamatova Aziza Do‘stmamat qizi (Western European Studies, 2025)
The adaptation of Oriental realities in Russian and English literary texts presents a fascinating study of cultural exchange, identity formation, and the representation of "the Other." Both literary traditions, shaped by historical, political, and social forces, have employed the Orient as a backdrop for exploring ideas of exoticism, colonialism, and cultural clash. This article examines the ways in which Eastern realities have been adapted and portrayed in Russian and English literature, highlighting key differences and similarities in the treatment of these themes. By exploring both literary traditions, we gain insight into the complex and often contradictory ways the East has been interpreted and reinterpreted in the Western imagination.
Keywords: Orientalism; Russian literature; English literature